2015
DOI: 10.1111/ssqu.12158
|View full text |Cite
|
Sign up to set email alerts
|

Mass Deportations and the Future of Latino Partisanship

Abstract: Objective. The U.S. government continues to deport large numbers of undocumented Latino immigrants. We address the likely effects of these policies on Latino partisanship. Methods. We use a survey experiment to test the effects of information about mass deportations on partisan evaluations among young second-generation Latinos. Results. Young U.S.-born Latinos view the Democratic Party as less welcoming when informed that deportations have been higher under President Obama than under his predecessor. Because m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Moreover, the results show that the relevant policy dimension for measuring polarization is immigration control, rather than the left-right continuum. 12 These findings are in line with previous studies showing that immigration control is of central importance in shaping immigrants' political orientations (Pantoja, Ramirez, and Segura 2001;Bowler, Nicholson, and Segura 2006;Street Abrajano and Alvarez 2010;Schildkraut 2013;Collingwood, Barreto, and Garcia-Rios 2014;, Zepeda-Millán, and Jones-Correa 2015) and that this policy dimension does not easily align with the left-right divide (Junn and Masuoka 2007;Hajnal and Lee 2011).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, the results show that the relevant policy dimension for measuring polarization is immigration control, rather than the left-right continuum. 12 These findings are in line with previous studies showing that immigration control is of central importance in shaping immigrants' political orientations (Pantoja, Ramirez, and Segura 2001;Bowler, Nicholson, and Segura 2006;Street Abrajano and Alvarez 2010;Schildkraut 2013;Collingwood, Barreto, and Garcia-Rios 2014;, Zepeda-Millán, and Jones-Correa 2015) and that this policy dimension does not easily align with the left-right divide (Junn and Masuoka 2007;Hajnal and Lee 2011).…”
supporting
confidence: 78%
“…In a study of Latino immigrants in the United States based on focus groups, Schildkraut (2013) found that when thinking about democracy in their adopted homeland, foreign-born residents consistently invoked their identity and experiences as immigrants rather than as members of their national-origin group or ethnic minorities, and did so even when questions made no mention of immigration (35-37). Moreover, many first-generation immigrants noted that they cared greatly whether their representatives paid attention to immigrants' needs and policy preferences and that these policies were not generic, such as education, crime, or the economy, but immigration specific, such as amnesty and deportation (Schildkraut 2013, 38; see also Pantoja, Ramirez, and Segura 2001;Bowler, Nicholson, and Segura 2006;Abrajano and Alvarez 2010, 37;Collingwood, Barreto, and Garcia-Rios 2014;Street, Zepeda-Millán, and Jones-Correa 2015).…”
Section: Party Polarization On Immigration Control and Partisanship Amentioning
confidence: 99%
See 1 more Smart Citation
“…The three largest historically underrepresented groups in Texas are Latinos, African Americans, and Asian Americans. While many Latinos have traditionally identified as Democrats than Republicans (with the exception of Cuban Americans), there are still questions about whether Latinos will continue identifying as Democrats (Street et al 2015). Street, Zepeda-Millán, and Jones-Correa investigated the impact of deportations during the Obama administration had on young US -born Latinos.…”
Section: Latinos African Americans and Asian Americansmentioning
confidence: 99%
“…Pro‐immigrant Republicans such as Jeb Bush make this argument (Bush and Bolick, ), as do Latino advocacy groups such as Latino Decisions (Barreto, ). There is also evidence that Latinos view the Democratic Party less favorably when that party is associated with restrictionist policies (Street, Zepeda‐Millán, and Jones‐Correa, ).…”
Section: The Sources Of Immigrant Party Identificationmentioning
confidence: 99%